The Effect of Gembili Flour Substitution (Dioscorea Esculenta L.) in the Making Roti Canai on Physical Quality and Sensory Quality - Nafisah Shofiyana Nursyabani; Alsuhendra Alsuhendra; Sachriani Sachriani (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to analyze the effect of substituting gembili flour in making roti canai on its physical quality and sensory properties. The study was conducted at the Pastry and Bakery Laboratory, Food Service Management Study Program, Jakarta State University, from July 2024 to August 2025. The research method used was an experiment, with samples of roti canai substituted with 20%, 25%, and 30% cassava flour. The results of the ANOVA test showed that there was no effect, while in terms of thickness, there was an effect of cooking loss, so it was followed by a Duncan test. The Duncan test results showed significant differences in each treatment. The 30% treatment had the highest average thickness of 12.45 mm. The results of the sensory quality analysis showed that there was no effect of treatment on the outer color, cassava aroma, samin oil aroma, cassava taste, savory taste, outer texture, inner texture, and layers, while in terms of inner color, there was an effect, so it was continued with Tuckey's test. The 30% treatment obtained the highest average in terms of outer color, inner color, gembili flavor, savory flavor, outer texture, inner texture, and layer. This study recommends 30% gembili flour substitution in roti canai as an effort to utilize local food ingredients.